A near 90-year record of the evolution of El Morado Glacier and its proglacial lake, Central Chilean Andes - Farias-Barahona, David; Wilson, Ryan; Bravo, Claudio; Vivero, Sebastian; Caro, Alexis; Shaw, Thomas E.; Casassa, Gino; Ayala, Alvaro; Mejias, Alonso; Harrison, Stephan; Glasser, Neil F.; McPhee, James; et al. (My University, 2020)
Using an ensemble of close- and long-range remote sensing, lake bathymetry and regional meteorological data, we present a detailed assessment of the geometric changes of El Morado Glacier in the Central Andes of Chile and its adjacent proglacial lake between 1932 and 2019. Overall, the results revealed a period of marked glacier down wasting, with a mean geodetic glacier mass balance of -0.39 +/- 0.15 m w.e.a(-1)observed for the entire glacier between 1955 and 2015 with an area loss of 40% between 1955 and 2019. We estimate an ice elevation change of -1.00 +/- 0.17 m a(-1)for the glacier tongue between 1932 and 2019. The increase in the ice thinning rates and area loss during the last decade is coincident with the severe drought in this region (2010-present), which our minimal surface mass-balance model is able to reproduce. As a result of the glacier changes observed, the proglacial lake increased in area substantially between 1955 and 2019, with bathymetry data suggesting a water volume of 3.6 million m(3)in 2017. This study highlights the need for further monitoring of glacierised areas in the Central Andes. Such efforts would facilitate a better understanding of the downstream impacts of glacier downwasting.
Keywords: glacier mass balance; glacier mapping; glacier hazards; glacier monitoring